Seminar on the second National Development Plan 15th to 18th March,1971 (Lagos : Federal ministry of information printing division, 1971)
This book is a seminar report on the second National Development Plan to provide a forum for top level executives in both the public and private sectors for the examination and exchange of views on various aspects of the second national development plan; to create a climate for better understanding and co-operation between the high level administrators and professional officers who are associated with the formulation and execution of government policies and the top managers and directors in the private sector.
ahz 19/03/2019
Loans
Keywords: National Development; Economic Development; Development plan; Nigeria